EFFICACY OF REPETITIVE TRANSCRANIAL MAGNETIC STIMULATION FOR PERSISTENT POSTURAL-PERCEPTUAL DIZZINESS: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Okhotan, Cindy Anastasia; Okhotan, Esther Ivana (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Persistent Postural-Perceptual Dizziness (PPPD) is a chronic functional vestibular disorder that significantly impairs quality of life. Conventional treatments often provide limited relief. Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising non-invasive adjunctive therapy for PPPD. Objective: To evaluate the efficacy of rTMS in reducing the severity of dizziness and associated psychological symptoms in patients with PPPD. Methods: A systematic review was conducted following PRISMA guidelines across six databases through August 2025. Randomized controlled trials (RCTs) comparing rTMS with sham stimulation or standard treatment were included. The primary outcome was dizziness severity, assessed using the Dizziness Handicap Inventory (DHI). Secondary outcomes included anxiety and depression severity, measured with the Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD). Pooled effect sizes were calculated as mean differences (MD) using fixed or random effects models. Results: Five RCTs comprising 332 participants were included. rTMS significantly reduced dizziness severity (DHI: MD = –16.60; 95% CI –21.58 to –11.62; p < 0.0001). It also decreased anxiety symptoms (HAMA: MD = –7.81; 95% CI –11.58 to –4.03; p < 0.0001) and alleviated depressive symptoms (HAMD: MD = –6.55; 95% CI –11.12 to –1.98; p < 0.0001). No serious adverse effects were reported. Conclusion: rTMS appears to be an effective and safe adjunctive treatment for PPPD, providing significant improvements in dizziness, anxiety, and depression. Larger, high-quality RCTs are warranted to refine stimulation protocols and assess long-term outcomes.